THE INFLUENCE OF CUSTOMER ORIENTATION ON MSME PERFORMANCE, WITH SOCIAL MEDIA ADOPTION AS A MODERATION VARIABLE (STUDY ON MSME CULINARY SECTOR IN PEKANBARU CITY) - Fauzi, M Fakhrur Rozi; Efnita, Yul (Jurnal Apresiasi Ekonomi, 2024)
The aim of this research is to examine the influence of customer orientationon MSME performance mediated by social media adoption. This research was conducted with a research sample of 115 respondents in the culinary sector of MSMEs in Pekanbaru City. This research adopts a quantitative approach with a descriptive point of view. Sampling is usually done randomly. Structural Equation Modeling software based on Partial Least Square (SEM-PLS). The results of this research show that customer orientation and social media adoption have a direct relationship with the performance of MSMEs. In an indirect relationship, customer orientation influences MSME performance through social media adoption. Keywords:     Customer orientation, performance, social media adoption